Junior Braves of the apocalypse. A brave is brave - Smith, Greg (Gregory K.) (Junior Braves of the apocalypse, 2018)
The Junior Braves of Tribe 65 return from a camping trip to find swarms of bloodthirsty mutants have overrun their town, bringing death and destruction everywhere they go! With their families missing and their homes destroyed, these plucky kids must use all their scouting talents, combined smarts, and teamwork to survive the end of the world! Junior Braves: A Brave is Brave is the beginning of an exciting, new, young adult graphic novel series that is one part Goonies and one part The Walking Dead, full of zombies, adventure, and handy tips for wilderness survival!